2022
DOI: 10.1111/bjdp.12403
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related qualitative differences in post‐error cognitive control adjustments

Abstract: Detecting an error signals the need for increased cognitive control and behavioural adjustments. Considerable development in performance monitoring and cognitive control is evidenced by lower error rates and faster response times in

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 84 publications
(109 reference statements)
4
17
1
Order By: Relevance
“…This is not surprising as the task blocks have always been considered to target various EF sub-processes. The fact that there was no consistent relation between post-error slowing and accuracy aligns with the literature showing that the relationship is far more complex than had been expected ( Wessel, 2012 ), depending mainly on the kind of conflict ( Danielmeier and Ullsperger, 2011 ; Dubravac et al, 2022 ), and the efficiency of cognitive control skills ( Chevalier et al, 2015 ; Roebers, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is not surprising as the task blocks have always been considered to target various EF sub-processes. The fact that there was no consistent relation between post-error slowing and accuracy aligns with the literature showing that the relationship is far more complex than had been expected ( Wessel, 2012 ), depending mainly on the kind of conflict ( Danielmeier and Ullsperger, 2011 ; Dubravac et al, 2022 ), and the efficiency of cognitive control skills ( Chevalier et al, 2015 ; Roebers, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…Large sample sizes as in the present case may contact low reliability but yet, the relatively small number of error and post-error trials per child remain a worry. At the same time, however, as a general psychology phenomenon post-error slowing both in children and adults seems to be present in any cognitive control task underlining that it is present, replicable, and worth being investigated (Dubravac et al, 2020(Dubravac et al, , 2022Thaqi and Roebers, 2020). Moreover, measurement problems associated with reaction times are ubiquitous in behavioral science, not limited to developmental research, but definitely serious (Draheim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-error slowing was also observed in tasks with demands on different cognitive control components and conflicts; for example, adults showed PES in both the Simon task, taxing cognitive flexibility in spatial conflict, and the Stroop task, taxing inhibition in semantic conflict (Dubravac et al, 2020;Forster & Cho, 2014;Notebaert & Verguts, 2011;Roebers, 2022;Wang et al, 2016). In children, only one previous study examined whether PES generalizes across distinct task demands with differing conflicts (Dubravac et al, 2022). This study tested children aged 8, 10, and 12 years and consistently found PES across three tasks: Stroop (Funny Fruits), Simon, and Flanker.…”
Section: Domain-general Versus Domain-specific Accounts Of Cognitive ...mentioning
confidence: 99%
“…In the current study, we investigated inhibition and cognitive flexibility (rule switching) demands in the contexts of spatial or semantic conflict. We used the Funny Fruits task (FF; Dubravac et al, 2022;Oeri et al, 2020) as a semantic conflict (S-S) task that requires mainly inhibition in its critical block. It also represents conflict between perceptual information, the visible color of a fruit stimulus, and semantic (conceptual) information, the fruit's actual color, that must be retrieved from memory.…”
Section: Domain-general Versus Domain-specific Accounts Of Cognitive ...mentioning
confidence: 99%